Define f ( x ) = k = 1 ∑ 1 0 0 1 k x k + 1 . If f ( 1 0 0 1 ) ( 1 0 0 ) can be evaluated as a × b ! where b is maximum, find a + b .
Bonus: If f ( x ) = k = 1 ∑ n k x k + 1 , find f ( n ) ( x ) .
Details and Assumptions:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I didn't get it.Why will the 1st (n-2) terms be zero ?
teree ma ka chdu
We know that by deriving 1001 times, only the terms 1 0 0 0 x 1 0 0 1 and 1 0 0 1 x 1 0 0 2 will survive (all the rest become constants and get a derivative of zero).
Now deriving them 1001 times, we get :
1 0 0 0 1 0 0 1 ! + 1 0 0 1 1 0 0 2 ! . 1 0 0 , where the 100 comes from the evaluation at x = 1 0 0 .
This simplifies to 9 9 9 ! . ( 1 0 0 1 + 1 0 0 2 . 1 0 0 . 1 0 0 0 ) , which gives us 100202000.
Let us Apply Taylor's Theorem in the region of
(
1
0
0
,
1
0
0
+
x
)
.
Let
f
(
x
)
=
∑
k
=
1
1
0
0
1
k
x
k
+
1
f ( 1 0 0 + x ) = f ( 1 0 0 ) + 1 ! x f ′ ( 1 0 0 ) + 2 ! ( x 2 ) f ′ ′ ( 1 0 0 ) +...... Now we just need to evaluate the coefficient of x 1 0 0 1 in the above expression which is ( 1 0 0 0 ) ( 1 0 0 1 ) 1 0 0 1 + ( 1 0 0 2 ) . 1 0 0 0 0 0 . Now multiply it by 1 0 0 1 ! to get ( 1 0 0 2 0 1 0 0 1 ) . ( 9 9 9 ! )
We know nth derivative of x^n = constant = n! So only last 2 term of series are useful and other are zero so We have- 1001 999!+1002 1000!*100 Solving we get 999!(100201001) Add them to get 100202000 And please specify in question that a,b are integers.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) f ′ ( x ) f ′ ′ ( x ) f 3 ( x ) f n ( x ) = k = 1 ∑ n k x k + 1 = k = 1 ∑ n k ( k + 1 ) x k = k = 1 ∑ n k ( k + 1 ) k x k − 1 = k = 1 ∑ n ( k + 1 ) ( k − 1 ) x k − 2 ⋯ ⋯ = k = 1 ∑ n ( k + 1 ) ( k − 1 ) ⋯ ( k − ( n − 2 ) ) x ( k − ( n − 1 ) )
Since first ( n − 2 ) terms of the summation will be zero we only have to calculate last two terms i.e:
= k = ( n − 1 ) ∑ n ( ( k + 1 ) ( k − 1 ) ⋯ ( k − ( n − 2 ) ) x ( k − ( n − 1 ) )
= n ( n − 2 ) ! + x ( n + 1 ) ( n − 1 ) ! = ( n − 2 ) ! ( n + x ( n + 1 ) ( n − 1 ) )
In the given question, n = 1 0 0 0 , x = 1 0 0 . Putting we get ( 9 9 9 ) ! × ( 1 0 0 2 0 1 0 0 1 ) . Hence answer = 9 9 9 + 1 0 0 2 0 1 0 0 1 = 1 0 0 2 0 2 0 0 0 .